UPAYA MENUMBUHKAN JIWA INTRAPRENEUR SISWA MELALUI MATERI KEWIRAUSAHAAN DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DI MTs SABILUL HUDA PONOROGO - Muhammad Widda Djuhan; Agus Trianto (MA'ALIM: Jurnal Pendidikan Islam, 2020)
This study aimed to determine the efforts to cultivate an intrapreneur spirit, the school's efforts to foster an intrapreneur spirit and the school's obstacles in cultivating an intrapreneur spirit. This type of research is a case study and the approach used by researchers is a qualitative approach. This research uses the research subjects of principals, teachers, students. Data collection techniques used in this study were: participatory observation, structured interviews and documentation. The analysis technique in this study uses data reduction, data presentation, drawing conclusions or verification. The results of this study there are still obstacles and obstacles in cultivating an intrapreneur spirit. Constraints that occur in the media and distribution of products that will be developed in entrepreneurial practice. so that it is still in the practice room and at the development stage. This discussion discusses the efforts of the teacher in processing the material, the efforts of the teacher. Student interest in class VII MTs Sabilul Huda, Karangjoho Village, Badegan District, Ponorogo Regency, there are learning problems with the enthusiasm of the students and the lack of enthusiasm for learning when implementing integrated social studies learning.